Productive behavior of corn hybrids (Zea mays, L.) for silage - Neumann, Mikael; Figueira, Danubia Nogueira [UNESP]; Faria, Marcos Ventura; Mendes, Marcelo Cruz; Carneiro, Murilo Klosovski (Univ Estadual Centro-oeste, 2015)
The experiment was conducted with the purpose of evaluating theproduction parameters from different corn hybrids for production silage: DKB-200; DKB-215; DKB-214; DKB-9034; DAS-120; DAS-599; DAS-766; DAS-522; AS-32; AS-3430; AS-3477; AS-1545; AG-5011; AG-6040; AG-6018; AG-8021; P-30F33; P-30P70; P-3021; P-30F53; SHS-4040; SHS-4060; GNZ-2005; e GNZ-2004. The ear first height showed amplitude of the 1.13 (DKB-215) at 1.69 m (P-30P70), while that plant height showed vary of the 2.06 (DKB-215) at 2.71 m (AG-8021). The green matter and dry matter production showed amplitude of the 47708 (DKB-215) at 66416 kg ha(-1) (AS-3430) and 20259 (DKB-215) at 28079 kg ha(-1) (AS-3430), respectively. The AS-3430 e AS-3477 hybrids showed low (P < 0.05) stay green (5.2 dry leaves of plant structure) compared of P-30F33 e AG-8021 (3.0 e 3.1 dry leaves, respectively). The DKB-200, DKB-214, DAS-120, DAS-599, AG-5011, P-30F33, P-30F53 and P-30P70 hybrids showed behavior tolerant at Pucciniasorghiand Phaeosphaeriamaydis (leaf area effect low of 24%), while AG-8021, SHS-4040 and SHS-4060 hybrids showed susceptible at disease (leaf area effect above of 40%). The addition analysis of the plant quantitative parameters, the DKB-214, DKB-9034, P-3021, P-30F53 and GNZ-2004 hybrids pronunced for silage production.
Keywords: composition of plant; dry matter production; sanity of plant; stay green